Apples are not the only fruit: The effects of concept typicality on semantic representation in the anterior temporal lobe - Woollams, Anna M. (Frontiers in Human Neuroscience, 2012)
Intuitively, an apple seems a fairly good example of a fruit, whereas an avocado seems less so. The extent to which an exemplar is representative of its category, a variable known as concept typicality, has long been thought to be a key dimension determining semantic representation. Concept typicality is, however, correlated with a number of other variables, in particular age of acquisition and name frequency. Consideration of picture naming accuracy from a large case-series of semantic dementia patients demonstrated strong effects of concept typicality that were maximal in the moderately impaired patients, over and above the impact of age of acquisition and name frequency. Induction of a temporary virtual lesion to the left anterior temporal lobe, the region most commonly affected in semantic dementia, via repetitive Transcranial Magnetic Stimulation produced an enhanced effect of concept typicality in the picture naming of normal participants, but did not affect the magnitude of the age of acquisition or name frequency effects. These results indicate that concept typicality exerts its influence on semantic representations themselves, as opposed to the strength of connections outside the semantic system. To date, there has been little direct exploration of the dimension of concept typicality within connectionist models of intact and impaired conceptual representation, and these findings provide a target for future computational simulation.